GENERATING STRUT-AND-TIE MODELS USING CONTINUUM AND DISCRETE TOPOLOGY OPTIMIZATION (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. Strut-and-tie models are largely used as an auxiliary tool in the design of reinforced concrete (RC) components with low shear span-to-depth ratio, such as deep beams, corbels,pile caps or joints. However, the generation of such models is still an open issue. This paperanalyses two optimization schemes, using the density and the discrete truss approaches. In both schemes, bi-linear models are used to represent the material behavior of the struts andthe steel reinforcing bars. Thus the separation of compressive and tensile load-carrying elements is achieved through an elastic model with a simple constitutive relationship for thecontinuum. Examples are provided demonstrating the potential value of the optimizationapproaches to RC design.Keywords: Strut-and-tie-models, reinforced concrete, topology optimization, density methods,ground structure.